Alter Game: A Study Protocol on a Virtual “Serious Game” for Relapse Prevention in Patients With Gambling Disorder - Giordano, Rosaria; Donati, Maria Anna; Zamboni, Lorenzo; Fusina, Francesca; Primi, Caterina; Lugoboni, Fabio (Frontiers in Psychiatry, 2022)
Cognitive behavioral therapy (CBT) is the most successful protocol in Gambling Disorder (GD) treatment. However, it presents some weaknesses, especially concerning Relapse Prevention (RP). RP is one of the most important therapeutic steps, aiming at managing cravings and to avoid future relapse increasing perceived self-efficacy. Encouraging results come from the blending of psychotherapy and virtual reality (VR)containing gambling cues. The goal of Alter Game (approved by the Ethical Commission, Prot. n. 69346), is verifying the efficacy of an innovative psychological treatment for GD based on the integration of traditional CBT therapy and an immersive VR cue exposure therapy using a serious virtual game, that is a game designed for purposes other than entertainment. RP in virtual cue-exposure therapy allows pathological gamblers to manage the urge to gamble and to avoid relapse by becoming aware of which internal and external triggers are related to craving. We hypothesize that the integrated intervention will be more effective than simple CBT with regards to self-efficacy, craving and gambling-related distortions. Four virtual ecological environments were developed, and a virtual app, Exludo, interfaced with a computerized multiparametric acquisition system for biofeedback, was created. A sample of about 60 patients aged between 18 and 65 with GD referring to the Addiction Medicine Unit of Verona (Rossi Hospital) will be recruited. Patients will be randomly assigned to the CBT group (16 CBT sessions) or the CBT + VR group (8 CBT sessions + 8 VR cue-exposure therapy sessions).. The MCMI-III, the BIS-11, and the SOGS will be used to evaluate inclusion and exclusion criteria, while the Gambling Related Cognitions Scale and the Multidimensional Gambling Self-Efficacy Scale will be used to verify changes as a function of the treatment. Craving will be evaluated through VAS and psychophysiological variables will be assessed through biofeedback. A pre-test/post-test experimental design with a 1-month follow-up will be conducted. This study will examine an innovative psychotherapeutic protocol for GD treatment, and it will help in identifying new virtual tools to increase the efficacy of traditional therapeutic approaches that could also be applied to treat other addictions.